PENGARUH LITERASI KEUANGAN, PENCATATAN KEUANGAN DAN PENGENDALIAN KEUANGAN TERHADAP KINERJA KEUANGAN PADA USAHA JAHIT DI KOTA JAMBI - Izro Maita; Titin Agustin Nengsih (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
The purpose of this study was to determine the effect of financial literacy, financial recording and financial control on financial performance in sewing businesses in Jambi City. Research using a quantitative approach, with data sources in the form of primary data. The sample in this study amounted to 90 respondents, with the sampling technique being purposive sampling. The results showed that financial literacy had a positive and significant effect on financial performance in sewing businesses in Jambi City, financial recording had a positive and significant effect on financial performance in sewing businesses in Jambi City, financial control had a positive and significant effect on financial performance in sewing businesses in Jambi City. Simultaneously financial literacy, financial recording, and financial control have a positive and significant effect on financial performance in sewing businesses in Jambi City. The variation in financial performance can be explained by financial literacy, financial recording and financial control by 60,7%.